Analysis of predictors of recurrent acute cardiovascular events in patients with acute coronary syndrome - E. I. Usova; L. M. Malishevsky; A. S. Alieva; T. А. Makarova; M. S. Alieva; A. N. Yakovlev; A. O. Conradi (Российский кардиологический журнал, 2024)
Aim. To assess the prevalence of traditional risk factors and analyze the predictors of recurrent cardiovascular events in patients with acute coronary syndrome (ACS).Material and methods. A total of 482 patients with ACS were included. The follow-up lasted three years. The composite endpoint (CE) included recurrent unstable angina, nonfatal myocardial infarction, repeated percutaneous coronary intervention (PCI), nonfatal ischemic stroke, hospitalization for decompensated heart failure, and cardiovascular death.Results. A high prevalence of traditional risk factors was revealed (dyslipidemia — 467 (96,9%), hypertension — 464 (96,3%), consumption of junk food — 450 (93,4%), sedentary lifestyle — 416 (86,3%)). During the three-year follow-up period, 90 patients had CE. Compared with patients without CE (n=392), patients with CE were significantly more likely to have a long-term CAD (69 (76,7%) vs 241 (61,5%), p=0,007), ACS accompanied by shortness of breath (50 (55,6%) vs 160 (40,9%), p=0,013); they had previously undergone myocardial revascularization (38 (42,2%) vs 116 (29,6%), p=0,024), often by PCI (36 (40,0%) vs 100 (25,5%), p=0,009), especially in the left main coronary artery (LMCA) (6 (6,7%) vs 3 (0,8%), p=0,002); they were more likely to develop in-hospital acute left ventricular failure (11 (12,2%) vs 18 (4,6%), p=0,012), had a lower hemoglobin level and hematocrit (p<0,05 for all); they more often required intensification of lipid-lowering therapy (86 (100%) vs 334 (85,2%), p=0,002), compliance with which was lower (6 (6,7%) vs 105 (26,8%), p<0,001) than in patients without CE. Previous intervention on the left coronary artery, non-compliance with lipidlowering therapy, hematocrit level 3 months and hemoglobin level 1 year after ACS were predictors of recurrent events. The combination of surgery on left coronary artery and non-compliance with lipid-lowering therapy demonstrated significantly less freedom from CE compared with other patients (77,4% vs 94,6%, p<0,001).Conclusion. A high prevalence of traditional risk factors in the population of patients with ACS was revealed, and potential predictors of recurrent cardiovascular events were identified.